(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
The present study aimed to investigate the reproductive biology of Labeobarbus altianalis from River Kuja-Migori basin, Kenya. This fish species is distributed in most water bodies in the Lake Victoria basin and effluent rivers. Labeobarbus altianalis is susceptible to fishing due to aggregation at the river mouths during reproduction seasons. We conducted a study for 18 months with an objective of determining length at 50% sexual maturity, fecundity, gonadosomatic index, egg size, sex ratio and breeding season of L. altianalis. The results showed that breeding of this fish occurred from March to August and September to November coinciding with longer and shorter rain seasons. Fecundity ranged from 1320-2382 eggs (mean 1552 ± 23.3). There was a strong correlation between fecundity and total length (R2 = 0.994). The mean egg diameter was 1.2 ± 0.007 mm. Mean gonado-somatic index was 5.63 ± 0.34 and 2.24 ± 0.21 for females and males respectively. The length at 50% sexual maturity was estimated to be 16.3 cm and 18 cm total length for males and females respectively. There was no significant difference in sex ratio from the hypothetical 1:1 (χ2, p > 0.05). Females had low fecundity and males attain sexual maturity earlier than females. Results from this study provide important information for managing riverine fishery in the Lake Victoria basin. Vol. 9, No. 2, August 2022: 221-228